Effects of Artisanal Mining on Land Degradation in Zamfara North-West, Nigeria - Goji, Richard Abel; Bala, Telzing Ponsak (ALSYS, 2024)
This paper analyzed the effects of artisanal mining on land degradation. It took critical look on both legal and illegal mining activities in the study areas and their level of devastated effects on land texture and structure over space. The method implored is both probability and non-probability approaches. The purposive targeted populations for the study were licensed and unlicensed small scale gold mining operators in the study areas, with a sample population of 100 person, and types of data used is both primary and secondary sources. Data was analyzed using descriptive statistic and frequency chart that indicated major challenges was illiteracy 31% and lack of coordination among miners 23%, major effect of land degradation was water pollution and deforestation had 30% and 23% respectively, and effects of artisanal mining on land degradation was degradation of arable land had 20% and exposing the soil to wind and chemical had 18%. It had a serious implication on ecosystem. The paper concluded that artisanal mining of mineral ores had caused serious damages on the land resources both soil and rivers. Therefore, to ensure sustainability in mining activities and to secure a quality environment, the following recommendations are hereby suggested, Educating local miners on the dangers of open cast mining and grinding of gold ore using the same grinder for grains to be consumed and Policy makers should avoid politicizing vital issues that will threaten peace and security of people in Zamfara and its environs.